In silico selection of Arabidopsis thaliana ecotypes with enhanced stress tolerance. - Prasch, Christian; Sonnewald, Uwe (Plant Signaling & Behavior, 2013)
Climate models predict increased occurrences of combined abiotic and biotic stress. Unfortunately, most studies on plant stress responses include single or double stress scenarios only. Recently, we established a multi-factorial system in Arabidopsis thaliana (Arabidopsis) to study the influence of simultaneously applied heat, drought, and virus. Our transcriptome analysis revealed that gene expression under multi-factorial stress is not predictable from single stress treatments. Combined heat and drought stress reduced expression of defense genes and genes involved in R-mediated disease responses, which correlated with increased susceptibility of Arabidopsis to virus infection. Eleven genes were found to be differentially regulated under all stress conditions. Assuming that regulated expression of these genes is important for plant fitness, Arabidopsis ecotypes were clustered according to their expression. Interestingly, ecotypes showing a close correlation to stressed Col-0 prior stress treatment showed improved growth under stress conditions. This result suggests a functional relevance of these genes in stress tolerance.

Signaling events in plants: Stress factors in combination change the picture - Prasch, Christian; Sonnewald, Uwe (Environmental and Experimental Botany, 2015)
Being sessile organisms, plants are constantly exposed to various kinds of environmental stimuli. To survive under unfavorable environmental conditions they have evolved strategies to allow a balance between growth, reproduction and survival. In this review article, we first focus on two major abiotic stress factors, drought and heat, and briefly summarize the current knowledge on signal transduction pathways involved in plant responses to these stresses. In nature it is unlikely that plants are exposed to abiotic or biotic stresses in isolation. Hence, multiple stress situations are more likely to occur including heat, drought, salinity and pathogen attack. Since in many cases stress responses are antagonistic, predictions of molecular responses to multiple stresses based on single stress data is difficult or even impossible. Only recently, researchers started to study multiple-stress interactions and discovered for instance that plant responses to a combination of heat and drought differ from those to both single stresses. Moreover, abiotic stress applications are likely to influence plant-pathogen interactions and vice versa. Here, we discuss various aspects of multiple stress applications published within the last few years and pronounce the importance to study biotic and abiotic stress combinations in order to predict plant responses to future climate changes. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Signaling; Heat stress; Drought stress; Biotic stress; Combined stress

Simultaneous Application of Heat, Drought, and Virus to Arabidopsis Plants Reveals Significant Shifts in Signaling Networks - Prasch, Christian; Sonnewald, Uwe (Plant Physiology, 2013)
Considering global climate change, the incidence of combined drought and heat stress is likely to increase in the future and will considerably influence plant-pathogen interactions. Until now, little has been known about plants exposed to simultaneously occurring abiotic and biotic stresses. To shed some light on molecular plant responses to multiple stress factors, a versatile multifactorial test system, allowing simultaneous application of heat, drought, and virus stress, was developed in Arabidopsis (Arabidopsis thaliana). Comparative analysis of single, double, and triple stress responses by transcriptome and metabolome analysis revealed that gene expression under multifactorial stress is not predictable from single stress treatments. Hierarchical cluster and principal component analyses identified heat as the major stress factor, clearly separating heat-stressed from nonheat-stressed plants. We identified 11 genes differentially regulated in all stress combinations as well as 23 genes specifically regulated under triple stress. Furthermore, we showed that virus-treated plants displayed enhanced expression of defense genes, which was abolished in plants additionally subjected to heat and drought stress. Triple stress also reduced the expression of genes involved in the R-mediated disease response and increased the cytoplasmic protein response, which was not seen under single stress conditions. These observations suggested that abiotic stress factors significantly altered turnip mosaic virus-specific signaling networks, which led to a deactivation of defense responses and a higher susceptibility of plants. Collectively, our transcriptome and metabolome data provide a powerful resource to study plant responses during multifactorial stress and allow identifying metabolic processes and functional networks involved in tripartite interactions of plants with their environment.

ß-amylase1 mutant Arabidopsis plants show improved drought tolerance due to reduced starch breakdown in guard cells. - Prasch, Christian; Ott, Kirsten; Bauer, Hubert; Ache, Peter; Hedrich, Rainer; Sonnewald, Uwe (Journal of Experimental Botany, 2015)
bam1 mutant plants impaired in stomatal starch degradation showed an improved drought tolerance associated with a down-regulation of guard cell-specific gene expression involved in water uptake and cell expansion.In plants, drought stress is a major growth limiting factor causing cell water loss through open stomata. In this study, guard cell-specific transcripts from drought-stressedArabidopsis plants were analysed and a down-regulation of beta-amylase 1 (BAM1) was found. In previous studies, BAM1 was shown to be involved in stomatal starch degradation under ambient conditions. Impaired starch breakdown ofbam1 mutant plants was accompanied by decreased stomatal opening. Here, it is shown that drought tolerance ofbam1 mutant plants is improved as compared with wild-type controls. Microarray analysis of stomata-specific transcripts frombam1 mutant plants revealed a significant down-regulation of genes encoding aquaporins, auxin- and ethylene-responsive factors, and cell-wall modifying enzymes. This expression pattern suggests that reduced water uptake and limited cell wall extension are associated with the closed state of stomata ofbam1 mutant plants. Together these data suggest that regulation of stomata-specific starch turnover is important for adapting stomata opening to environmental needs and its breeding manipulation may result in drought tolerant crop plants.
Keywords: Arabidopsis; beta-amylases; drought; guard cells; starch